Preimplantation genetic testing practices in the Nordic countries. (2nd March 2020) - Hreinsson, Julius; Iwarsson, Erik; Hanson, Charles; Grøndahl, Marie Louise; Løssl, Kristine; Hydén‐Granskog, Christel; Ingerslev, Hans Jakob; ,
Abstract: Introduction: Preimplantation genetic testing (PGT) is growing in importance and volume internationally. International societies such as the European Society for Human Reproduction and Embryology compile international results and these data are published in scientific journals. We present the first compilation of practices, quality measuress and outcome data from Nordic clinics performing PGT. Material and methods: We conducted a structured online survey of PGT practices in the Nordic countries to compare clinical and laboratory techniques, outcomes and quality measures applied in Nordic clinics. The survey was designed by the authors and answered by the authors and members of the study group. The outcome data represents results from 2018. Results and details were clarified through iteration with responding clinics while maintaining anonymity. Response rate in the study was 80%, with 8 of 10 clinics performing PGT responding. Results: Most of the PGT cycles in the Nordic countries are funded through the public healthcare system with University Hospitals performing the majority of treatments, 716/848, or 84.4%, of oocyte retrievals in this dataset. The genetic analyses are in five cases performed by the affiliated local genetic laboratory, and the remaining three consult with large international private enterprise laboratories. Genetic counseling is widely used. Results in the Nordic clinics compare well with international data. Systematic quality control procedures are in place and the larger clinics and laboratories utilize ISO certification or accreditation in the quality management. Automatic witnessing with detailed electronic documentation of laboratory processes is not utilized in the responding clinics, although a majority uses manual witnessing procedures in the laboratory. The outcome after PGT in terms of clinical pregnancy per transfer is around 40% per embryo transfer and compares well with international data. Conclusions: Preimplantation genetic testing is organized in rather few clinics in the Nordic countries and most of them use local laboratories for genetic analyses of the biopsies. Laboratory procedures are largely in accordance with international guidelines and the outcome after PGT in terms of clinical pregnancy per transfer is comparable to results in international reports.